Humanising Education: The Guideline on Sejahtera Academic Framework (SAF) for Well-Being Community - Haque, A. K. M. Ahasanul; Sarker, Md Atiqur Rahman (Kulliyyah of Economics and Management Sciences, 2021)
Education is more than studying for examinations and getting ready for employability and satisfying industry needs. Rather, education now a days incorporates 4Ms (Manpower, Mind, Machine and Market). Education with soul and loaded with values and wisdom can nurture the humanising process that makes individual and professional achieve sustainable development goals. Sejahtera in this regard focuses on well-being of community in collaboration with parties for achieving community lifestyle. Sejahtera Academic Framework (SAF) emphasizes that humanising the education system with values of life along with spiritual knowledge brings peace and harmony into the community. These two ensures sustainable life style for a balanced and harmonious relationship among people. Thus, achieving the wellbeing of the society. This descriptive study focuses on the importance of humanising the education through SAF guidelines.